Cultivation of shiitake mushroom - Bautista, Rankine Glorioso F. (College of Engineering, 1993)
Product: Shiitake mushroom -- Plant capacity: Fresh mushroom - 40 kg/day, Dried mushroom - 50 kg/day -- Plant site: Lucban, Quezon -- Land area: 50 x 65 sq.m. -- Total capital investment: P 11,914,335 -- Return on investment: 44.06 % (after tax) -- Payback period: 2.1 years (after tax)